Individual differences in brain attention networks: the challenge of indexing temporal change - Matthews, Gerald; Kustubayeva, Almira; Zholdassova, Manzura; Borbassova, Gulnur (Frontiers in Cognition, 2025)
The vigilance decrement in speed and accuracy of response is prevalent in studies of sustained attention. The amplitudes of Event-Related Potentials (ERPs) elicited by task stimuli also show temporal decline. However, it is difficult to link the behavioral performance decrement to loss of efficiency in the specific brain circuits that control human attention. A recent study published by the authors used an extended duration-version of the Attention Network Test to explore temporal changes in behavioral and electroencephalographic indices in executive control, alerting, and orienting attention networks. This study found evidence for temporal decline in ERPs associated with the alerting network, as well as slowing of uncued reaction time. This study, like most psychophysiological studies of sustained attention, analyzed group data. The present article provides new analyses of data from the authors' previous study to investigate individual differences in loss of attention on the extended ANT, and their relationships with positive and negative affect. Data analyses addressed the temporal stability of attention network metrics, inter-relationships between different metrics, and associations between metrics and affective states. Results illustrated some challenges in assessment of brain networks at the individual level on tasks requiring sustained attention. Issues included differential temporal stability of metrics, divergence of behavioral and ERP measures, and distinguishing changes in network function from changes in baseline response. The ANT is well-supported by group data as a tool for investigating attentional functioning. However, the present results suggest that caution is necessary in utilizing network indices at the individual level in clinical and other applied contexts.